2022
DOI: 10.3233/jad-220249
|View full text |Cite
|
Sign up to set email alerts
|

Evoked Cortical Depolarizations Before and After the Amyloid Plaque Accumulation: Voltage Imaging Study

Abstract: Background: In Alzheimer’s disease (AD), synaptic dysfunction is thought to occur many years before the onset of cognitive decline. Objective: Detecting synaptic dysfunctions at the earliest stage of AD would be desirable in both clinic and research settings. Methods: Population voltage imaging allows monitoring of synaptic depolarizations, to which calcium imaging is relatively blind. We developed an AD mouse model (APPswe/PS1dE9 background) expressing a genetically-encoded voltage indicator (GEVI) in the neo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…In addition, GEVI ArcLight-MT was used to map the propagation of epileptic seizures in a mouse model in vivo using two-photon voltage imaging, allowing seizure progression and local voltage dynamics to be revealed [ 196 ]. Recently, Zhu et al [ 198 ] studied synaptic dysfunction in Alzheimer’s disease using population voltage imaging on the slices of chi-VSFP transgenic animals. In this study voltage imaging revealed early-onset hyperexcitability in L2/3 pyramidal neurons, with significantly longer halfwidths of voltage transient in the Alzheimer’s disease group compared to those of the controls and older age groups.…”
Section: Experimental Studies With Gevis In Vertebratesmentioning
confidence: 99%
“…In addition, GEVI ArcLight-MT was used to map the propagation of epileptic seizures in a mouse model in vivo using two-photon voltage imaging, allowing seizure progression and local voltage dynamics to be revealed [ 196 ]. Recently, Zhu et al [ 198 ] studied synaptic dysfunction in Alzheimer’s disease using population voltage imaging on the slices of chi-VSFP transgenic animals. In this study voltage imaging revealed early-onset hyperexcitability in L2/3 pyramidal neurons, with significantly longer halfwidths of voltage transient in the Alzheimer’s disease group compared to those of the controls and older age groups.…”
Section: Experimental Studies With Gevis In Vertebratesmentioning
confidence: 99%